GENERAL ASPECTS OF BOVINE WORMS AND THEIR OCCURRENCE IN THE STATE OF GOIÁS, BRAZIL - Margarida, Luiz Henrique Batista; da Silva, Victoria Helena Pomponi; Oliveira, Lucas Eterno Francisco; Coelho, Karyne Oliveira; Taveira, Rodrigo Zaiden; Neto, Osvaldo José da Silveira (Seven Editora, 2024)
Bovine worm is an infection of great importance for Brazilian and world livestock. The damage caused by parasitosis sometimes escapes reality and when it is noticed, it brings incalculable inconvenience. The control of parasites, whether gastrointestinal or pulmonary, must be part of a routine to be followed with great discretion and rigor by the rural property. Several studies demonstrate the economic impact and damage caused by worms. Financial figures are impressive about the size of the losses caused by parasites in cattle. In the state of Goiás, studies referring to Hepatic Fasciola are demonstrated in very significant data, as well as studies on Bovine Cysticercosis. Being careful and judicious in the use of anthelmintics is one of the main points to be observed in the established chemical management, in order to avoid resistance by parasites. It is important to know how to define the specific anthelmintic for the problem and target population. Biological management is used on a smaller scale in Brazil. To be successful in treatments, it is important to know the epidemiology and correctly apply the forms of control. There are several laboratory techniques available that can help in the correct diagnosis of parasitosis; Considering that most of them, because they are subclinical, are hardly perceived in everyday life in a visual way. Adequate sanitary management, adoption of efficient prophylactic measures with short-term results, bring numerous positive increases to the development of production animals. Establishing prophylactic calendars and instituting specific control programs for each situation or region converge to the consolidation of better gains at a lower cost. DOI:https://doi.org/10.56238/sevened2024.037-005